Strategic Recommendations in Increasing Gen Z User Engagement towards Gamification Elements with Fuzzy AHP and Octalysis Approaches - Marisa, Fitri; Ahmad, Sharifah Sakinah Syed; Handajani, Endah Tri Esti; NoerTjahyana, Agustinus; Maukar, Anastasia L; Istiadi, - (Society of Visual Informatics, 2025)
Generation Z (Gen Z), often referred to as the